Human Gait Detection Using Silhouette Image Recognition - et. al., Dr. MD.Javeed Ahammed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s world biometric has taken a wide role in human’s life. So, there is an advance in this field among which Gait recognition approach is in major interest by which person identification has became an easy task. In this paper a OU-ISIR database case is used by which silhouette extraction from a blurred image made possible. Moving image parameters such as west size, hip size, foot size, step size etc. can be extracted and it can be matched to the data in our database, which was used to identify culprits by detectives, in most of the cases it proved helpful also if data is not available in data base then also its helpful itself for finding the exact gender or age of that suspect. The method of gender classification is used in this paper where amount of people are assigned as human observers who predicts by seeing the silhouette image parameters such as hair, style, chest, hip, dressing etc from the picture. The techniques used for gender identification but for age detection our OU-ISIR is used. In our paper there is a 2 groups of peoples as child and adult.